Contratos inteligentes y certificados auténticos para trámites productivos en el sector público peruano orientado en un servicio de calidad al ciudadano - Luciani Lujan, Richard Michael (2019)
In this innovation work, design thinking focused on citizens and public officials was applied. When analyzing corruption, they indicated the desire to disappear, but they feel and perceive that it is impossible, instead, they consider that digital attention in procedures can improve productivity. The legal framework in Peru for the application of this technology in the public sector was analyzed to proceed with the changes and improvements. Its institutions have contemplated the impact of blockchain and cryptocurrencies for their regulations. An estimate was made of the costs for loss of time in the procedures, micro-corruption costs and the projected costs of corruption in 2019. The cost estimate was also made to implement the project to solve the above costs, obtaining that the technological solution is cheaper than the costs of corruption and time, justifying the investment in this technology. The immutable maintenance of records was verified by a citizen and by systems personnel of a public institution, this does not apply to smart contracts.